Therapeutic considerations for individuals with communication difficulties and co-morbid challenges (2019)
The comorbidity nature of communication difficulties and associated developmental challenges often times impair the overall functional ability and quality of life, learning and psycho-social behaviours, and health stability of those with the conditions, especially the children. With the attendant effect of those comorbid challenges, children would experience delayed language development, reduced vocabulary, poor clarity of speech, poor word recall, difficulty forming sentences, poor understanding of spoken speech, difficulty following instructions, poor empathy, poor ability to express needs/feelings, literal understanding/speech, repetitive speech, swallowing problems, poor listening skills and poor copying/imitation skills. Therefore, the management of such communication difficulties and associated developmental challenges in children is a complex task requiring professional competence and expertise, experience, a blend of therapeutic options and multidisciplinary team-work approach. It is against this background that this paper highlighted the benefits of different therapeutic options for both children and adults with comorbidity of communication difficulties and developmental challenges. The need for multidisciplinary team-work services in rehabilitating the conditions has also been emphasized. The paper concluded by advocating cooperative efforts of the allied professionals and combined therapeutic options towards rehabilitating comorbid communication and developmental challenges.